Asymptomatic and symptomatic urethral gonorrhoea in men who have sex with men attending a sexual health service. (August 2017) - Ong, J.J.; Fethers, K.; Howden, B.P.; Fairley, C.K.; Chow, E.P.F.; Williamson, D.A.; Petalotis, I.; Aung, E.; Kanhutu, K.; De Petra, V.; Chen, M.Y.
Abstract: Objectives: Guidelines regarding whether men who have sex with men (MSM) without symptoms of urethritis should be screened for urethral gonorrhoea differ between countries. We examined the rate of asymptomatic urethral gonorrhoea in MSM using sensitive nucleic acid amplification testing. Methods: This study was conducted on consecutive MSM attending the Melbourne Sexual Health Centre between July 2015 and May 2016 for sexually transmitted infections screening. Gonorrhoea testing with the Aptima Combo 2 (AC2) assay was performed on all urine specimens obtained from MSM, whether symptoms of urethritis were present or not. Men were classified as having: typical discharge if they reported symptoms suggesting purulent discharge; other symptoms if they reported other symptoms of urethritis; and no symptoms if they reported no urethral symptoms. Results: During the study period, there were 7941 clinic visits by 5947 individual MSM with 7090 urine specimens obtained from 5497 individual MSM tested with the AC2 assay. Urethral gonorrhoea was detected in 242 urine specimens from 228 individual MSM. The majority (189/242, 78%, 95% CI 73–83) reported typical discharge, 27/242 (11%, 95% CI 8–16) reported other urethral symptoms, and 26/242 (11%, 95% CI 7–15) reported no symptoms on the day of presentation and testing. Among men with urethral gonorrhoea, the proportions with concurrent pharyngeal or rectal gonorrhoea were 32% (134/210) and 64% (74/235), respectively. The mean interval between last reported sexual contact and onset of typical urethral discharge, where present, was 3.9 days. Conclusion: The findings from our study lend support to guidelines that recommend screening asymptomatic MSM for urethral gonorrhoea.